Study of pile friction capacity in soft clay soil based on laboratory scale model. - Azhari, Ridho Ary; Rusdiansyah, Rusdiansyah (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Banjarmasin City is an area with a type of soil with a low bearing capacity known as peat soil or soft clay. Wooden pile foundation which is the most frequently used choice in buildings in this city, relies on the principle of attachment or friction to support the structure. Following the discussion, this method has significant Differential Settlement risks. In the case of pile foundation, changes in shear strength of soil have an impact on bearing capacity of pile, such as modifications in soil water content. The first scenario during this study included wetting the object for 1 day and draining it for 2, 4, and 8 days. The second phase was wetting the test object for 3 days and drying it for 2, 4, and 8 days. Additionally, the third scenario was immersing the object for 5 days and draining it for 2, 4, and 8 days and also forming an object with the original water content. A loading test and an unconfined compression test were later conducted.Based on the total analysis results, increasing internal water content generally reduced friction bearing capacity (Qs) of pile. Increasing water content caused soil cohesion to decrease, changing the distance between particles and reducing shear strength of soil. Moreover, shear strength capacity of soil was weakened due to an increase in water content, enlarging the pores, and also reducing soil density.